Kidney Biopsy Findings in a Patient With Valproic Acid-Associated Fanconi Syndrome. (July 2019) - Singer, Pamela; Sethna, Christine B; Castellanos-Reyes, Laura; Yaskiv, Oksana; Bijol, Vanesa
A 7-year-old boy with a history of febrile illness-related epilepsy syndrome presented with proteinuria and elevated creatinine. His severe epileptic disorder has been treated since age 2 with multiple antiepileptic medications, including valproic acid. More recently, he was noted to have features of Fanconi syndrome with acidosis, hypophosphatemia, hypokalemia, glucosuria, and nephrotic-range proteinuria. This was managed with supplements; however, in the setting of rising creatinine and prominent proteinuria, a kidney biopsy was performed. Renal cortex revealed markedly decreased expression of proximal tubule markers and increased expression of markers of distal nephron differentiation. Such findings have been described in several genetic and acquired conditions, including renal tubular dysgenesis, severe hypoxic injury following renal artery stenosis, and toxic injury related to in utero exposure to angiotensin-converting-enzyme inhibitors. Such changes have not been reported before in valproic acid-associated Fanconi syndrome, although in general, morphologic findings in this condition have not been well established in the literature.